2019
DOI: 10.1590/1678-4685-gmb-2018-0099
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of pregnancies with prenatal diagnosis of Trisomy 18 or Trisomy 13: Retrospective cases of a 23-year experience in a Brazilian public hospital

Abstract: Trisomy 18 (T18) and trisomy 13 (T13) are polymalformative syndromes associated with a high rate of spontaneous abortions, intrauterine death, and short postnatal life. This study describes the overall outcome in a country where the therapeutic interruption of pregnancy is not available. The medical records of women with prenatal diagnosis of full trisomy of T13 or T18 between October 1994 and October 2017 were analyzed in order to describe their natural outcomes. Thirteen cases of T13 and 29 cases of T18 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
0
4
0
2
Order By: Relevance
“…Although there are many published studies on survival rates of patients born with T18, these vary widely with reported live birth and 1‐year survival rates of 20%–90% and 0%–30%, respectively. 14 , 17 , 18 , 19 , 20 Older studies relied on population registries and many of the patients were diagnosed postnatally, while more recent studies included prenatally diagnosed patients. Postnatal diagnosis has been hypothesised to be one of the main factors resulting in longer survival rates, presumably because more interventions are performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many published studies on survival rates of patients born with T18, these vary widely with reported live birth and 1‐year survival rates of 20%–90% and 0%–30%, respectively. 14 , 17 , 18 , 19 , 20 Older studies relied on population registries and many of the patients were diagnosed postnatally, while more recent studies included prenatally diagnosed patients. Postnatal diagnosis has been hypothesised to be one of the main factors resulting in longer survival rates, presumably because more interventions are performed.…”
Section: Discussionmentioning
confidence: 99%
“…While earlier studies often included more postnatally diagnosed patients, all our patients had a prenatal diagnosis of T18, as is the case in more recent studies. 18 , 19 , 22 The South African Choice of Termination of Pregnancy act No 92 of 1996 26 allows for TOP for severe malformations up to term. TOP rates for T18 vary widely, and the rate in our study of 52% was lower than that of many reports from countries which, like ours, have liberal termination of pregnancy policies 5 , 6 , 27 reflecting the overall low acceptance rate of TOP in our country.…”
Section: Discussionmentioning
confidence: 99%
“…based study in a high-income country [3]. In Brazil, there is no specific guideline for the perinatal management of newborn infants with Trisomy 13 or 18 and many of them do not receive active care, resulting in early deaths [33]. This study has several limitations.…”
Section: Plos Onementioning
confidence: 95%
“…De esta manera, no se centra solo en la corta expectativa de vida, sino en el valor que significa el tiempo compartido con ese hijo. En la bibliografía revisada se constata que es frecuente que los médicos trasmitan a los padres una visión más negativa que la real (35), e incluso que insistan en la elección del aborto (24,25,29,35,36,37). Se ha des-crito que, para los padres, las mayores lesiones son las causadas por la actitud de algunos médicos y la forma en que comunican el diagnóstico (36).…”
Section: Comunicación Del Diagnósticounclassified
“…Entre la bibliografía consultada en esta investigación, se encuentra el "consenso de la rama genética de la Sociedad Pediátrica Chilena", que recomienda el aborto en fetos con determinadas patologías (42). Algunos autores también se manifiestan abiertamente a favor del aborto, ensalzando la autonomía de la mujer (17,37). De esta forma, la misma medicina, que por vocación está destinada al cuidado de la vida, se contradice a sí misma.…”
Section: La Aceptación Del Aborto En El áMbito Médicounclassified